Mizoroki-Heck reaction over palladium nanoparticles supported on WO3 - Amini, Mojtaba; Heydarloo, Dina Bahrami; Rahimi, Mohammad; Kim, Min Gyu; Gautam, Sanjeev; Chae, Keun Hwa (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Palladium nanoparticles supported on metal oxide WO3 were synthesized and the physicochemical properties of compounds were characterized by X-ray diffraction (XRD), X-ray absorption near edge spectroscopy (XANES) at O and Pd IC-edges, energy dispersive X-ray analysis (EDX), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The catalytic activity of compounds in the carbon-carbon coupling reactions of aryl halides with olefins (Mizoroki-Heck reaction) was studied. The catalyst can be easily separated from the reaction mixture and reused after washing without reduction in activity. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: CROSS-COUPLING REACTIONS; PD NANOPARTICLES; HETEROGENEOUS CATALYSIS; ELECTRONIC-STRUCTURE; ORGANIC-CHEMISTRY; ACTIVE CATALYST; COMPLEXES; ARYLATION; EFFICIENT; LIGAND